Efficient face detection for multimedia applications - Tsapatsoulis, Nicolas; Avrithis, Yannis; Kollias, Stefanos D. (My University, 2000)
Face detection is becoming an important tool in the framework of many multimedia applications. Several face detection algorithms based on skin color characteristics have appeared in the literature. Most of them have generalization problems due to the skin color model they use. We present a study which attempts to minimize the generalization problem by combining the M-RSST color segmentation algorithm with a Gaussian model of the skin color distribution and global shape features. Moreover by associating the resultant segments with a face probability we can index and retrieve facial images from multimedia databases
Keywords: Image processing; Face--Identification; Algorithms; Databases; Multimedia systems